Preparation method of nanoscale silicon dioxide alcohol-soluble sol

By using polyacrylic acid and anhydrous ethanol to form micelles under high concentrations of ammonia, and then adding tetraethyl orthosilicate, the traditional Stober method is solved by synthesising nanoscale silica for a long reaction time, poor spherical shape and sol in the traditional Stober method. The problem of instability has achieved rapid and efficient preparation of nano-scale silica alcohol-soluble sols.

CN119430196APending Publication Date: 2025-02-14HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD

Patent Information

Application Number
CN202411833829.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

Smart Images

  • Figure CN119430196A_ABST
    Figure CN119430196A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano material preparation, and particularly relates to a preparation method of nanoscale silicon dioxide alcohol-soluble sol. The method comprises the following steps: dissolving a water-soluble polymer in an ammonia water solution, and then adding absolute ethyl alcohol to form a polymer micelle; adding tetraethyl orthosilicate into the micelles, obtaining a nanoscale silicon dioxide nanoparticle mixed solution after the reaction is finished, then dispersing the nanoscale silicon dioxide nanoparticle mixed solution in deionized water through centrifugation, then centrifuging to obtain pure silicon dioxide particles, dispersing the pure silicon dioxide particles in absolute ethyl alcohol, adding a silane coupling agent KH570 at the same time, and performing ultrasonic dispersion to obtain the nanometer silicon dioxide nanoparticles. And carrying out ultrasonic dispersion to obtain the nanoscale silicon dioxide alcohol-soluble sol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation, and relates to a method for preparing nano-scale silicon dioxide alcohol-soluble sol. Background Art

[0002] Silica nanomaterials are widely used in the fields of architecture, polymer composite membranes, optical imaging, catalysis, adsorption, batteries, etc. due to their good stability, easy functionalization, good biocompatibility, large specific surface area, etc. The performance of these applications is highly dependent on the size of the particles, and silica particles of different particle sizes have different properties and uses.

[0003] The traditional method for synthesizing silica nanoparticles is the Stober method (W. A.Fink, E.Bohn, Controlled growth of monodisperse silica spheres in the micron size range, J.Colloid Interface Sci.26 (1968) 62-69.), the obtained silica particles are of controllable size, good dispersibility, and mild reaction conditions. This method can adjust the particle size by the concentration of the alkaline catalyst. As the alkaline catalyst increases, the particle size of the silica will also increase. However, nano-scale silica needs to reduce the concentration of the alkaline catalyst, which will cause some problems, such as: 1. The reduction of the catalyst content will greatly prolong the reaction time. The prior art (CN109081608B) uses the Stober method to synthesize 10-50nm SiO2 nanoparticles with a reaction time of 6 to 8 hours and aging for 3-7 days. 2. As the catalyst content decreases, the smaller the size of the silica, the worse the sphericity. In addition, there are a large number of pores on the surface, which further increases the surface energy of the nano-scale silica particles, resulting in the instability of the nano-scale silica sol, the particles are easy to agglomerate, and the sol is easy to precipitate or form a gel. Summary of the invention

[0004] The present invention provides a method for preparing nano-scale silicon dioxide alcohol sol to overcome the drawbacks of the prior art. The method can synthesize nano-scale silicon dioxide particles under high concentration ammonia water conditions, and has a short reaction time, good spherical shape and high surface density.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a nano-scale alcohol-soluble silica sol, comprising the following steps:

[0006] S1. dissolving a water-soluble polymer in an aqueous ammonia solution, heating to 30-50° C., and stirring to obtain an alkaline solution of the water-soluble polymer; the water-soluble polymer is polyacrylic acid; and the mass fraction of the aqueous ammonia solution is 25.0-28.0%;

[0007] S2, adding anhydrous ethanol to step S1, stirring to form a water-soluble polymer micelle solution;

[0008] S3, lowering the water bath temperature of the water-soluble polymer micelle solution in step S2 to room temperature, then adding tetraethyl orthosilicate, and obtaining a mixed solution of silica nanoparticles after the reaction is completed;

[0009] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, adding deionized water for ultrasonic dispersion after removing the liquid, and centrifuging the mixed solution after ultrasonic dispersion to obtain silica nanoparticles; adding anhydrous ethanol and silane coupling agent KH570 without drying, and ultrasonically dispersing to obtain a silica alcohol-soluble sol with a diameter of 15 to 54 nm.

[0010] As an improved technical solution of the present application, the polyacrylic acid is selected from one of polyacrylic acid with a molecular weight of Mw3000 and polyacrylic acid with a molecular weight of Mw5000, or a combination of the two in any mass ratio.

[0011] As an improved technical solution of the present application, the addition amounts of the water-soluble polymer and ammonia water described in step S1 are: 0.3-0.6 parts by mass, 10-20 parts by mass respectively;

[0012] The amount of anhydrous ethanol added in step S2 is 50 to 120 parts by mass;

[0013] The addition amount of tetraethyl orthosilicate in step S3 is 0.6 to 1.2 parts by mass respectively;

[0014] The added amounts of anhydrous ethanol and silane coupling agent KH570 in step S4 are 5 to 10 parts by mass and 0.1 to 0.3 parts by mass, respectively.

[0015] As an improved technical solution of the present application, the stirring time of step S1 is 5 to 10 minutes, the stirring time of step S2 is 5 to 10 minutes, the reaction time of step S3 is 30 to 60 minutes, and the total reaction time of steps S1, S2 and S3 is 40 to 80 minutes.

[0016] As an improved technical solution of the present application, the addition rate of tetraethyl orthosilicate in step S3 is 0.5-2 ml / min.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) Compared with the traditional Stober method, when the concentration of the alkaline catalyst is too high, the size of the silica particles synthesized by the traditional method is larger. In the present invention, after polyacrylic acid is dissolved in an alkaline solution, anhydrous ethanol is added, which causes the polyacrylic acid to form micelles. When tetraethyl orthosilicate is added, these micelles will block their collision to form larger particles. Even when the concentration of the alkaline catalyst is too high, only nano-sized silica can be formed.

[0019] (2) Compared with the traditional Stober method for synthesizing nano-scale silica, the content of the alkaline catalyst in this method is higher, the synthesized nano-scale silica is better spherical, and the surface of the silica is more dense. In addition, the content of the alkaline catalyst is much higher than that of the traditional method, which will greatly shorten the reaction time. The traditional method requires 6 to 8 hours, while the present invention only requires 40 to 80 minutes.

[0020] (3) This method selects a water-soluble polymer, polyacrylic acid, as a synthesis auxiliary agent. The polymer has good water solubility and can be washed with deionized water and then removed by centrifugation after the reaction is completed, thereby obtaining pure nano-scale silica nanoparticles.

[0021] (4) Since the silica particles have good sphericity and a denser surface, their surface energy is lower than that of mesoporous silica particles, so the alcohol-soluble sol prepared by the particles has better stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a transmission electron microscope photograph of the silicon dioxide synthesized in Comparative Example 1;

[0023] Figure 2 is a transmission electron microscope photograph of the silicon dioxide synthesized in Comparative Example 2;

[0024] Figure 3 is a transmission electron microscope photograph of the silicon dioxide synthesized in Comparative Example 3;

[0025] Figure 4 This is a transmission electron microscope photograph of the nano-scale silicon dioxide synthesized in Example 1. DETAILED DESCRIPTION

[0026] The present application prepares the nano-scale silica alcohol-soluble sol by dissolving a water-soluble polymer in an ammonia solution to obtain a water-soluble polymer alkaline solution; then adding anhydrous ethanol to form polymer micelles. Then, tetraethyl orthosilicate is added to the micelles, and after the reaction is completed, a mixed solution of nano-scale silica nanoparticles is obtained, which is then dispersed in deionized water by centrifugation and then centrifuged to obtain pure silica particles, which are then dispersed in anhydrous ethanol and silane coupling agent KH570 is added at the same time, and nano-scale silica alcohol-soluble sol is obtained by ultrasonic dispersion. In fact, under the conditions of high-concentration ammonia water (mass fraction 25.0-28.0%), silica nanoparticles with a diameter of 15-54nm are quickly synthesized and prepared into an alcohol-soluble sol.

[0027] In the preparation process, the water-soluble polymer is one of polyacrylic acid (Mw-3000) and polyacrylic acid (Mw-5000) or a combination of the two in any mass ratio. After polyacrylic acid is dissolved in an alkaline solution, anhydrous ethanol is added to form micelles of polyacrylic acid. When tetraethyl orthosilicate is added, these micelles will block the collision to form larger particles. Even when the alkali catalytic concentration is too high, only nano-scale silica can be formed, and the average diameter of the obtained nano-scale silica nanoparticles is 15-54nm.

[0028] The above method obtains a nano-scale alcohol-soluble silica sol, which is transparent, has a Tyndall effect, and does not produce precipitation when placed at room temperature for 2 months.

[0029] Specifically, a method for preparing a nano-scale silica alcohol sol comprises the following steps:

[0030] S1. Dissolve a water-soluble polymer in an ammonia solution, heat to 30-50° C., and stir to obtain an alkaline solution of the water-soluble polymer; the water-soluble polymer is polyacrylic acid; and the mass fraction of the ammonia solution is 25.0-28.0%.

[0031] S2, adding anhydrous ethanol to step S1, stirring to form a water-soluble polymer micelle solution;

[0032] S3, lowering the water bath temperature of the water-soluble polymer micelle solution in step S2 to room temperature, then adding tetraethyl orthosilicate, and obtaining a mixed solution of silica nanoparticles after the reaction is completed;

[0033] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, adding deionized water for ultrasonic dispersion after removing the liquid, centrifuging the mixed solution after ultrasonic dispersion, and obtaining silica nanoparticles; adding anhydrous ethanol and silane coupling agent KH570 without drying, and ultrasonic dispersion to obtain nano-scale silica alcohol-soluble sol. When forming the alcohol-soluble sol in S4, adding a silane coupling agent can improve the stability of the sol. At the same time, the silane coupling agent KH570 can modify the surface of the silica particles to make them more stable in the sol. In addition, the polyacrylic acid micelles are soluble in water and can be washed with deionized water to obtain pure silica nanoparticles.

[0034] The nano-scale alcohol-soluble silica sol of the present application refers to an alcohol-soluble silica sol having an average diameter of 15 to 54 nm.

[0035] The total stirring time and reaction time for the preparation of the nano-sized silica particles is 40 to 80 minutes, which indicates that the synthesis time of the nano-sized silica particles is short.

[0036] As an improved technical solution of the present application, the polyacrylic acid is selected from one of polyacrylic acid with a molecular weight of Mw3000 and polyacrylic acid with a molecular weight of Mw5000, or a combination of any mass ratio.

[0037] As an improved technical solution of the present application, the addition amounts of the water-soluble polymer and ammonia water described in step S1 are respectively: 0.3-0.6 parts by mass and 10-20 parts by mass; wherein the water-soluble polymer content is less than 0.3 parts by mass, the micelles formed are small and it is difficult to block the growth of silica, while the content of the water-soluble polymer is higher than 0.6 parts by mass, the mixed solution will precipitate. The content of ammonia water is lower than 10 parts by mass, the reaction time will increase, while the content of ammonia water is higher than 20 parts by mass, the particle size of silica will increase.

[0038] The amount of anhydrous ethanol added in step S2 is 50 to 120 parts by mass. The amount of ethanol added will affect the concentration of aqueous ammonia. When the amount of ethanol added is small, the concentration of aqueous ammonia will increase. Ammonia is a catalyst, and an increase in concentration will increase the reaction rate, and vice versa, it will reduce the reaction rate.

[0039] The addition amount of tetraethyl orthosilicate in step S3 is 0.6-1.2 parts by weight. If the content of tetraethyl orthosilicate is too low, the formed silicon dioxide particles will be poorly shaped, while if the content of tetraethyl orthosilicate is too high, the particle size of silicon dioxide will be increased.

[0040] The added amounts of anhydrous ethanol and silane coupling agent KH570 in step S4 are 5 to 10 parts by mass and 0.1 to 0.3 parts by mass, respectively.

[0041] As an improved technical solution of the present application, the stirring time of step S1 is 5 to 10 minutes, the stirring time of step S2 is 5 to 10 minutes, the reaction time of step S3 is 30 to 60 minutes, and the total reaction time of steps S1, S2 and S3 is 40 to 80 minutes. This indicates that the total reaction time for synthesizing small-size SiO2 particles in the present technical solution is relatively short.

[0042] As an improved technical solution of the present application, the addition rate of tetraethyl orthosilicate in step S3 is 0.5-2 ml / min. The addition rate of tetraethyl orthosilicate in the preparation of the above-mentioned nano-scale silica alcohol sol is 0.5-2 ml / min. When the addition rate is too slow, silica will grow on the outer layer of the polyacrylic acid micelle, and after washing with deionized water, a hollow Si O2 structure will be formed. If the addition rate is too fast, the particle size of silica will increase.

[0043] The present invention will be further described below in conjunction with the embodiments.

[0044] Example 1

[0045] This embodiment provides a method for preparing a nano-scale silica alcohol sol, which specifically comprises the following steps:

[0046] S1, dissolving 0.3 parts by mass of polyacrylic acid (Mw-5000) in 10 parts by mass of aqueous ammonia solution, heating to 30°C, and stirring for 5 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0047] S2, adding 50 parts by mass of anhydrous ethanol to step S1, and stirring for 5 minutes to form a water-soluble polymer micelle solution;

[0048] S3, lowering the water bath temperature of the mixed solution in step S2 to 25° C., then adding 0.6 parts by mass of tetraethyl orthosilicate at a rate of 0.5 ml / min, reacting for 30 minutes, and then obtaining a mixed solution of nano-scale silica nanoparticles;

[0049] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, and pouring off the liquid; then adding deionized water and ultrasonically dispersing, and centrifuging again to obtain silica nanoparticles, and then adding 5 parts by mass of anhydrous ethanol and 0.1 parts by mass of silane coupling agent KH570 without drying, and then ultrasonically dispersing to obtain a silica alcohol-soluble sol with an average diameter of 22 nm.

[0050] According to the above method, a nano-scale silica alcohol-soluble sol is obtained. Figure 4This is a transmission electron microscope photo of the silica sol in Example 1. It can be seen from the figure that the average size of the silica is about 22nm. When the alkaline concentration in this example is high, the particle size of the silica is small and the spherical shape is good. The surface is dense, and the dispersibility of the silica in the sol is good, and it can be stably stored for two months without precipitation.

[0051] Example 2

[0052] This embodiment provides a method for preparing a nano-scale silica alcohol sol, which specifically comprises the following steps:

[0053] S1, dissolving 0.6 parts by mass of polyacrylic acid (Mw-3000) in 20 parts by mass of aqueous ammonia solution, heating to 50° C., and stirring for 10 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0054] S2, adding 120 parts by mass of anhydrous ethanol to step S1, and stirring for 10 minutes to form a water-soluble polymer micelle solution;

[0055] S3, lowering the water bath temperature of the mixed solution in step S2 to room temperature, then adding 1.2 parts by mass of tetraethyl orthosilicate at a rate of 2 ml / min, reacting for 60 min, and then obtaining a mixed solution of silica nanoparticles;

[0056] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, pouring out the liquid, then adding deionized water and ultrasonically dispersing, centrifuging again to obtain silica nanoparticles, then adding 10 parts by mass of anhydrous ethanol and 0.3 parts by mass of silane coupling agent KH570 without drying, and then ultrasonically dispersing to obtain a silica alcohol-soluble sol with an average diameter of 54 nm.

[0057] According to the above method, a nano-scale alcohol-soluble silica sol is obtained. The average size of the silica is about 54 nm. The silica in the sol has good dispersibility and can be stably stored for two months without precipitation.

[0058] Example 3

[0059] This embodiment provides a method for preparing a nano-scale silica alcohol sol, which specifically comprises the following steps:

[0060] S1, dissolving 0.4 parts by mass of polyacrylic acid (Mw-5000) in 12 parts by mass of aqueous ammonia solution, heating to 40°C, and stirring for 8 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0061] S2, adding 120 parts by mass of anhydrous ethanol to step S1, and stirring for 10 minutes to form a water-soluble polymer micelle solution;

[0062] S3, lowering the water bath temperature of the mixed solution in step S2 to room temperature, then adding 0.8 parts by mass of tetraethyl orthosilicate at a rate of 1 ml / min, reacting for 40 minutes, and then obtaining a mixed solution of silica nanoparticles;

[0063] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, pouring off the liquid, then adding deionized water and dispersing by ultrasonication, centrifuging again to obtain silica nanoparticles, then adding 8 parts by mass of anhydrous ethanol and 0.2 parts by mass of silane coupling agent KH570 without drying, and then dispersing by ultrasonication to obtain a silica alcohol-soluble sol with an average diameter of 15 nm.

[0064] According to the above method, a nano-scale alcohol-soluble silica sol is obtained. The average size of the silica is about 15 nm. The silica in the sol has good dispersibility and can be stably stored for two months without precipitation.

[0065] Example 4

[0066] This embodiment provides a method for preparing a nano-scale silica alcohol sol, which specifically comprises the following steps:

[0067] S1, dissolving 0.3 parts by mass of polyacrylic acid (Mw-3000) in 15 parts by mass of aqueous ammonia solution, heating to 30°C, and stirring for 10 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0068] S2, adding 60 parts by mass of anhydrous ethanol to step S1, and stirring for 10 minutes to form a water-soluble polymer micelle solution;

[0069] S3, lowering the water bath temperature of the mixed solution in step S2 to room temperature, then adding 0.6 parts by mass of tetraethyl orthosilicate at a rate of 2 ml / min, reacting for 60 min, and then obtaining a mixed solution of silica nanoparticles;

[0070] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, pouring out the liquid, then adding deionized water and ultrasonically dispersing, centrifuging again to obtain silica nanoparticles, then adding 10 parts by mass of anhydrous ethanol and 0.3 parts by mass of silane coupling agent KH570 without drying, and then ultrasonically dispersing to obtain a silica alcohol-soluble sol with an average diameter of 24 nm.

[0071] According to the above method, a nano-scale alcohol-soluble silica sol is obtained. The average size of the silica is about 24 nm. The silica in the sol has good dispersibility and can be stably stored for two months without precipitation.

[0072] Example 5

[0073] This embodiment provides a method for preparing a nano-scale silica alcohol sol, which specifically comprises the following steps:

[0074] S1, dissolving 0.3 parts by mass of polyacrylic acid (Mw-5000) in 18 parts by mass of aqueous ammonia solution, heating to 50° C., and stirring for 10 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0075] S2, adding 60 parts by mass of anhydrous ethanol to step S1, and stirring for 10 minutes to form a water-soluble polymer micelle solution;

[0076] S3, lowering the water bath temperature of the mixed solution in step S2 to room temperature, then adding 1.2 parts by mass of tetraethyl orthosilicate at a rate of 2 ml / min, reacting for 60 min, and then obtaining a mixed solution of silica nanoparticles;

[0077] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, pouring out the liquid, then adding deionized water and ultrasonically dispersing it, and centrifuging it again to obtain silica nanoparticles, and then adding 10 parts by mass of anhydrous ethanol and 0.3 parts by mass of silane coupling agent KH570 without drying, and then ultrasonically dispersing it to obtain a silica alcohol-soluble sol with an average diameter of 33 nm.

[0078] According to the above method, a nano-scale alcohol-soluble silica sol is obtained. The average size of the silica is about 33 nm, and the silica in the sol has good dispersibility and can be stably stored for two months without precipitation.

[0079] Comparative Example 1

[0080] This comparative example provides a method for synthesizing a silicon dioxide alcohol sol by a Stober method, which specifically comprises the following steps:

[0081] S1. Mix 1 part by mass of tetraethyl orthosilicate and 25 parts by mass of anhydrous ethanol, and stir magnetically for 5 minutes at room temperature to prepare solution A.

[0082] S2, 2 parts by mass of water, 2 parts by mass of aqueous ammonia and 25 parts by mass of anhydrous ethanol were mixed, and stirred at room temperature for 2-3 minutes to prepare solution B;

[0083] S3, slowly adding the same volume of solution A to solution B to prepare a reaction precursor solution;

[0084] S4. Place the reaction precursor solution in a constant temperature water bath at 30°C and stir the reaction for 7 hours to obtain an alcohol-silica alcohol-soluble sol.

[0085] Figure 1 The transmission electron microscope photo of the silica sol in Comparative Example 1 shows that the average size of silica is about 25 nm, the formability is poor, and the surface is loose with a large number of pores. In addition, the particles are easy to agglomerate. The result of Comparative Example 1 is that nano-sized silica nanoparticles can only be obtained when the alkali concentration is very low.

[0086] Comparative Example 2

[0087] This comparative example provides a method for synthesizing silicon dioxide by the Stober method, which specifically comprises the following steps:

[0088] S1. Mix 1 part by mass of tetraethyl orthosilicate and 25 parts by mass of anhydrous ethanol, and stir magnetically for 5 minutes at room temperature to prepare solution A.

[0089] S2, 1 part by mass of water, 5 parts by mass of aqueous ammonia and 25 parts by mass of anhydrous ethanol were mixed, and stirred at room temperature for 2-3 minutes to prepare solution B;

[0090] S3, slowly adding the same volume of solution A to solution B to prepare a reaction precursor solution;

[0091] S4. Place the reaction precursor solution in a constant temperature water bath at 30°C and stir the reaction for 7 hours to obtain an alcohol-silica alcohol-soluble sol.

[0092] Figure 2 The transmission electron microscope photo of the silica sol in Comparative Example 2 shows that the average size of the silica is about 92 nm. The results of Comparative Example 2 show that when the alkaline concentration is high, the particle size increases significantly.

[0093] Comparative Example 3

[0094] This comparative example provides a method for synthesizing silicon dioxide, which specifically comprises the following steps:

[0095] S1, dissolving 0.3 parts by mass of polyacrylic acid (Mw-5000) in 10 parts by mass of aqueous ammonia solution, heating to 30°C, and stirring for 5 minutes to make it more evenly dispersed, to obtain a water-soluble polymer alkaline solution;

[0096] S2, adding 50 parts by mass of anhydrous ethanol to step S1, and stirring for 5 minutes to form a water-soluble polymer micelle solution;

[0097] S3, lowering the water bath temperature of the mixed solution in step S2 to room temperature, then adding 0.6 parts by mass of tetraethyl orthosilicate at a rate of 0.1 ml / min, reacting for 30 minutes, and then obtaining a mixed solution of silica nanoparticles;

[0098] S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, pouring out the liquid, then adding deionized water and dispersing it ultrasonically, and centrifuging it again to obtain silica nanoparticles, and then adding 5 parts by mass of anhydrous ethanol and 0.1 parts by mass of silane coupling agent KH570 without drying, and then dispersing it ultrasonically to obtain a nano-scale silica alcohol-soluble sol.

[0099] Figure 3 The transmission electron microscope photo of the silica sol in Comparative Example 3 shows that the silica is a spherical broken structure. Why is it broken? (When the concentration of ammonia water is high, the catalytic reaction rate is fast, and the silicon source will quickly form SiO2. When the concentration of ammonia water is low, the catalytic reaction will slow down, causing the silicon source to slowly attach to the polyacrylic acid micelles and deposit. When the deposition is not uniform, after the reaction is completed, the water-soluble polyacrylic acid will be washed away and the broken SiO2 will be left.)

[0100] It can be seen from the experimental results of the above comparative examples and embodiments that the present invention has prepared a method for preparing a nano-scale silica alcohol-soluble sol.

[0101] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a nano-scale silica alcohol sol, characterized in that: The steps include: S1. dissolving a water-soluble polymer in an aqueous ammonia solution, heating to 30-50° C., and stirring to obtain an alkaline solution of the water-soluble polymer; the water-soluble polymer is polyacrylic acid; and the mass fraction of the aqueous ammonia solution is 25.0-28.0%; S2, adding anhydrous ethanol to step S1, stirring to form a water-soluble polymer micelle solution; S3, lowering the water bath temperature of the water-soluble polymer micelle solution in step S2 to room temperature, then adding tetraethyl orthosilicate, and obtaining a mixed solution of silica nanoparticles after the reaction is completed; S4, centrifuging the mixed solution of silica nanoparticles obtained in step S3, adding deionized water for ultrasonic dispersion after removing the liquid, and centrifuging the mixed solution after ultrasonic dispersion to obtain silica nanoparticles; adding anhydrous ethanol and silane coupling agent KH570 without drying, and ultrasonically dispersing to obtain a silica alcohol-soluble sol with a diameter of 15 to 54 nm.

2. The method for preparing a nano-silicon dioxide alcohol sol according to claim 1, characterized in that: The polyacrylic acid is selected from one of polyacrylic acid with a molecular weight of Mw 3000 and polyacrylic acid with a molecular weight of Mw 5000, or a combination of the two in any mass ratio.

3. The method for preparing a nano-silicon dioxide alcohol sol according to claim 1, characterized in that: The amounts of the water-soluble polymer and ammonia water added in step S1 are 0.3-0.6 parts by mass and 10-20 parts by mass respectively; The amount of anhydrous ethanol added in step S2 is 50 to 120 parts by mass; The addition amount of tetraethyl orthosilicate in step S3 is 0.6 to 1.2 parts by mass respectively; The added amounts of anhydrous ethanol and silane coupling agent KH570 in step S4 are 5 to 10 parts by mass and 0.1 to 0.3 parts by mass, respectively.

4. The method for preparing a nano-silicon dioxide alcohol sol according to claim 1, characterized in that: The stirring time of step S1 is 5 to 10 minutes, the stirring time of step S2 is 5 to 10 minutes, the reaction time of step S3 is 30 to 60 minutes, and the total reaction time of steps S1, S2 and S3 is 40 to 80 minutes.

5. The method for preparing a nano-silicon dioxide alcohol sol according to claim 1, characterized in that: The addition rate of tetraethyl orthosilicate in step S3 is 0.5-2 ml / min.

Citation Information

Patent Citations

  • Outdoor SiO2 Superhydrophilic Nanocoating and its Preparation Method

    CN109081608B

Cited By

  • Photovoltaic glass surface hydrophobic treatment process

    CN120887655A

  • High-wear-resistance nano filler modified rubber material and preparation method thereof

    CN122011534A

  • High wear-resistant nano-filler modified rubber material and preparation method thereof

    CN122011534B